Evaluasi Ketahanan Sumber Daya Genetik Kedelai terhadap Cekaman Salinitas - Putri, Pratanti Haksiwi; Anggoro Susanto, Gatut Wahyu; Taufiq, Abdullah (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Soybean (Glycine max (L.) Merr.) is sensitive to salinity stress. The availability of soybean cultivar tolerant to salinity stress is the main key of succeeding of soybean cultural practice on saline affected land. Objective of the research was to evaluate the resistance of soybean germplasms to salinity stress. The research was conducted on saline affected soil in Lamongan District during the dry season (May-August) 2016. Nineteen soybean genotypes that were selected from previous salinity test in the green house were reevaluated in the field using a randomized block design with three replications. Wilis cultivar (sensitive to salinity) used as check. Variable observations consisted of soil properties before planting, number of plant grow at 13 and 41 days after sowing (DAS), plant height at 41, 56 and 71 DAS, chlorophyll content index at 27, 41 and 56 DAS, soil EC at 71 DAS, number of harvested plants, yield and yield components. The results showed that among 19 genotypes tested, only five genotypes that survived up to harvest with plant population 30-50% at high salinity level. Salinity reduced plant population more than 50%, and plant height only 50% from its normal height. Based on soil EC, plant population at harvest, and yield, genotype Karat 13, Grayak 3 and Grayak 5 were identified adaptive to high salinity level with soil EC 11,7-14,4 dS/m, while MLGG 0160 were identified adaptive to moderate salinity level with soil EC up to 9,1 dS/m.